2023
DOI: 10.5114/ceh.2023.127400
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infections and fever after hepatocellular carcinoma ablation therapy: predictive role of procalcitonin

Abstract: Aim of the study Hepatocellular carcinoma (HCC) is a leading cause of mortality among patients with liver cirrhosis. According to the current practice guidelines, different ablations are used either as curative or palliative therapies. The current study aimed at determining bacterial infections as causes of fever and the predictive role of procalcitonin (PCT) among patients with HCC who had ablation therapy. Material and methods This cross sectional study was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Procalcitonin (PCT) is a component of the body's systemic inflammatory response and its changes serve as a reminder to clinicians of the patient's level of systemic inflammatory activity. In the study by Abdelkader A [16] and others, PCT was identified as an important indicator of bacterial infection and fever. When the body is subjected to bacterial infection, especially by Gram-negative bacteria, procalcitonin significantly increases.…”
Section: Discussionmentioning
confidence: 97%
“…Procalcitonin (PCT) is a component of the body's systemic inflammatory response and its changes serve as a reminder to clinicians of the patient's level of systemic inflammatory activity. In the study by Abdelkader A [16] and others, PCT was identified as an important indicator of bacterial infection and fever. When the body is subjected to bacterial infection, especially by Gram-negative bacteria, procalcitonin significantly increases.…”
Section: Discussionmentioning
confidence: 97%